2011
DOI: 10.1371/journal.pone.0016771
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Dihydroceramides from Common Human Bacteria Are Recovered in Human Tissues

Abstract: Novel phosphorylated dihydroceramide (PDHC) lipids produced by the periodontal pathogen Porphyromonas gingivalis include phosphoethanolamine (PE DHC) and phosphoglycerol dihydroceramides (PG DHC) lipids. These PDHC lipids mediate cellular effects through Toll-like receptor 2 (TLR2) including promotion of IL-6 secretion from dendritic cells and inhibition of osteoblast differentiation and function in vitro and in vivo. The PE DHC lipids also enhance (TLR2)-dependent murine experimental autoimmune encephalomyeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 20 publications
(32 reference statements)
1
68
0
Order By: Relevance
“…In addition to P. gingivalis proteins and LPS penetrating gingival tissue, P. gingivalis phosphorylated dihydoceramide lipids have been isolated from gingival tissue and subgingival plaque of chronic periodontitis patients (52)(53)(54). Whole P. gingivalis cells and certain components, including the RgpA-Kgp complexes and lipids, induce secretion of a number of proinflammatory cytokines from epithelial and fibroblast cells in vitro, such as IL-1, IL-6, IL-8, PGE 2 , macrophage chemoattractant protein (MCP)-1a, and ICAM-1 (50,54,55).…”
mentioning
confidence: 99%
“…In addition to P. gingivalis proteins and LPS penetrating gingival tissue, P. gingivalis phosphorylated dihydoceramide lipids have been isolated from gingival tissue and subgingival plaque of chronic periodontitis patients (52)(53)(54). Whole P. gingivalis cells and certain components, including the RgpA-Kgp complexes and lipids, induce secretion of a number of proinflammatory cytokines from epithelial and fibroblast cells in vitro, such as IL-1, IL-6, IL-8, PGE 2 , macrophage chemoattractant protein (MCP)-1a, and ICAM-1 (50,54,55).…”
mentioning
confidence: 99%
“…Instead, we reported that a unique fatty acid constituent of both lipid A and LPS of P. gingivalis, called 3-hydroxy isobranched C 17:0 (3-OH iso C 17: 0), exists in lipid products recovered predominantly from organic solvent extracts of subgingival plaque, periodontally diseased tissues, and diseased teeth, with little recovered in aqueous extracts of these samples (26,29). Since LPS partitions essentially only into the aqueous phase with this extraction technique (39), we concluded that LPS of P. gingivalis and other related Bacteroidetes bacteria (33), including Prevotella intermedia and Tannerella forsythia, is not present to a significant extent in diseased periodontal tissues. By analogy, it is presumed that LPS from nonBacteroidetes subgingival organisms also does not contaminate diseased periodontal tissues.…”
mentioning
confidence: 98%
“…The possibility exists that the 3-OH iso C 17:0 recovered from organic extracts of subgingival plaque samples and periodontally diseased tissues could include free lipid A species devoid of the O-polysaccharide component of LPS. The first aim of this investigation was to isolate lipid A from P. gingivalis, and after characterization of the molecular structures using matrix-assisted laser desorption ionization tandem mass spectrometry (MALDI-MS/MS) and electrospray-MS/MS, we determined whether the dominant phosphorylated lipid A species are present in lipid extracts of periodontally diseased teeth and subgingival plaque samples.The phosphorylated dihydroceramide lipid classes of P. gingivalis that promote proinflammatory reactions and morphological changes in fibroblasts (31) are also readily detected on periodontally diseased teeth (32) and are recovered from gingival tissue samples from periodontitis sites (26,32,33). This observation is important because the phosphorylated dihydroceramide lipids of P. gingivalis are reported to engage Toll-like receptor 2 (TLR2) when promoting dendritic cell secretion of interleukin-6 (IL-6) (29) and inhibiting osteoblast function and mineral deposition in vivo and in vitro (43).…”
mentioning
confidence: 99%
See 2 more Smart Citations